2010
DOI: 10.3892/mmr.2010.375
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of glioma-associated oncogene 1 expression and its correlation with the expression of sonic hedgehog, E-cadherin and S100a4 in human hepatocellular carcinoma

Abstract: Abstract. The aim of the present study was to analyze the mrna and protein expression of glioma-associated oncogene 1 (Gli1) in hepatocellular carcinoma (Hcc) and its correlation with sonic hedgehog (Shh), one of the ligands of hedgehog (Hh) signaling, and two epithelial-mesenchymal transition (eMT) markers, e-cadherin and S100a4. We also investigated the potential crosstalk between Hh signaling and eMT in Hcc. Paired Hcc and normal tumor-adjacent tissues were freshly collected from 30 primary Hcc patients. Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
(12 reference statements)
2
12
0
Order By: Relevance
“…The cell apoptosis in the xenograft tissues was measured by TUNEL assay according to the manufacturer’s guidelines. The details of IHC protocal have been described previously [22]. …”
Section: Methodsmentioning
confidence: 99%
“…The cell apoptosis in the xenograft tissues was measured by TUNEL assay according to the manufacturer’s guidelines. The details of IHC protocal have been described previously [22]. …”
Section: Methodsmentioning
confidence: 99%
“…A line of evidences have revealed that EMT modulates malignant characteristics of cancer cells such as mobility, invasion, anti-apoptosis and stem-liking phenotypes[23]. Our previous studies showed that EMT appeared frequently in HCC and was involved in increased migration and invasion ability of HCC cells[24], [25]. In addition, we demonstrated that GLI1 overexpression was responsible for EMT phenotype of HCC and indispensable for TGFβ1-driven EMT of HCC cells[24].…”
Section: Introductionmentioning
confidence: 72%
“…IHC staining was performed as described previously[25]. Briefly speaking, the paraffin slides were dewaxed and dehydrated.…”
Section: Methodsmentioning
confidence: 99%
“…Zheng et al . found that Gli1 protein expression was positively correlated with Shh and S100a4, and negatively correlated with E-cadherin [42]. EMT is regulated by several transcription factors, including Snail, ZEB1, ZEB2, Twist1, and Twist2, each of which bind to the E-cadherin promoter region and repress its transcription [43-49].…”
Section: Discussionmentioning
confidence: 99%